The Top Tail of the Wealth Distribution in Germany, France, Spain, and Greece - Stefan Bach; Andreas Thiemann; Aline Zucco (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this study we analyze the top tail of the wealth distribution in Germany and France based on the Household Finance and Consumption Survey (HFCS). Since top wealth is likely to be underrepresented in household surveys we integrate the big fortunes from rich lists, estimate a Pareto distribution, and impute the missing rich. As a result, the top percentile share of household wealth in Germany jumps up from 24 percent based on the HFCS alone to 34 percent after top wealth imputation. For France there is only a small effect of the imputation since rich households are better captured in the survey.
Keywords: D31; C46; C81; 330